RANCANG BANGUN MESIN CETAK ECO PAVING BLOCK PNEUMATIK BERBASIS LIMBAH PLASTIK - Kusmayadi, Adi; Sukroni, Sukroni; Haris, Emin; Irawan, Candra; Rohmat, Yusup Nur; Syaifurrahman, Arief; Gunawan, Leo Van; Ghozali, Muhamad (P3M Politeknik Negeri Indramayu, 2025)
The escalating volume of plastic waste has become a critical environmental challenge, highlighting the need for innovative solutions to repurpose it into valuable construction materials. This study aimed to design and develop a pneumatic-based eco-paving block printing machine that uses plastic waste as its primary raw material. The research methodology encompassed the design and simulation of pneumatic circuits, structural analysis involving stress distribution, displacement, and factor of safety (FOS), and strength testing of the fabricated eco-paving blocks. The machine was equipped with a pneumatic cylinder measuring 80 × 75 mm, operating at a pressure of 6 bar and generating a maximum pressing force of 300 kg. The simulation results confirmed that the maximum stress and displacement remained within safe limits, with a minimum FOS of 8.4, thereby ensuring a stable and reliable design. Testing of the eco-paving blocks revealed compressive strengths ranging from 38 to 54 MPa, surpassing the requirements of the SNI 03-0691-1996 standard. This study demonstrates that a pneumatic-based eco-paving block printing machine effectively transforms plastic waste into high-quality construction materials compliant with national standards, offering a practical solution to the plastic waste crisis while promoting sustainability in the construction industry.